ANALISIS PERTIMBANGAN MAJELIS HAKIM ATAS PENGADUAN ATAU LAPORAN PALSU (Studi Kasus Putusan Nomor : 10/Pid.B/2023/PN.Tul) - Monica Atma Negara; Margo Hadi Pura (Yustitia, 2025)
ABSTRACT This research aims to identify the elements that constitute a false report and analyze how the judges consider cases of false complaints. Through a normative legal approach, this study found that false reports are characterized by elements such as "whoever", "intentionally", "submitting a false complaint or notification to the authorities", and "both in writing and for writing". In the case of Abdul Halik Roroa, a lawyer who was reported for making a false report, is an interesting example. Although proven guilty, the defendant was acquitted because the judges were of the view that his actions were carried out in the course of performing his professional duties in good faith. This decision indicates that there is legal protection for lawyers while carrying out their duties. Keywords: Elements, Considerations, Panel of judges.